Laju Degradasi Beberapa Jenis Plastik Menggunakan Ulat Hongkong (Tenebrio molitor L.) dan Ulat Jerman (Zophobas atratus F.): Degradation Rate of Several Plastics Type Using Mealworm (Tenebrio molitor L.) and Germany Superworm (Zophobas atratus F.) - INDRA PUTRA, ICHSAN LUQMANA; MA’RUFAH, NILA (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2022)
ABSTRACT Excessive consumption of plastic material causes a higher amount of plastic waste, which causes environmental pollution. This study aims to determine the degradation rate of several types of plastics using Tenebrio molitor and Zophobas atratus in the laboratory. The research was conducted from September 2020–March 2021 at the Ecology and Systematic Laboratory, Faculty of Applied Science and Technology, Ahmad Dahlan University, Yogyakarta. The study used 10 of the 6th instar caterpillars with five repetitions. The treatment was used three types of plastic samples, namely: Polypropylene (PP), High-Density Polyethylene (HDPE) and Low-Density Polyethylene (LDPE), each of which was given as much as 1 gram. The control treatment was given 1 gram of bran feed. Each caterpillar was measured for its body weight and length every three days and carried out for 30 days. The data results were analyzed statistically inferential at the 5% confidence level. The parameters observed were the increase in length and weight of T. molitor and Z. atratus, degradation rate, and the Waste Reduction Index (WRI). The highest average length value for larvae was T. molitor HDPE plastic (1.83 cm), and the lowest was LDPE (1.41 cm), while body weight measurements showed constant weight values (0.07 gr). Size of the length of larvae Z. atratus showed the highest average body length value for LDPE plastic (3.70 cm) and the lowest in control (3.46 cm), while the weight gain showed an average range of 0.41–0.43 grams. The counting of values of degradation rate and WRI obtained the highest to lowest results, respectively, namely, control (0.075), PP (0.011), LDPE (0.009), and HDPE (0.007) in T. molitor. While the values of degradation rate and WRI in Z. atratus were control (0.038), PP (0.032), LDPE (0.014), and HDPE (0.004). For the WRI, in T. molitor, the highest was control (2.51%), and lowest was HDPE (0.22%), while in Z. atratus, the highest was control (1.26%), and lowest was HDPE (0.12%). Keywords: Degradation, HDPE, LDPE, Tenebrio molitor, Zophobas atratus ABSTRAK Konsumsi berlebih terhadap bahan plastik mengakibatkan jumlah sampah plastik semakin tinggi sehingga menyebabkan pencemaran lingkungan. Oleh karena itu, perlu adanya sebuah upaya untuk mengurangi sampah plastik secara alami. Penelitian ini bertujuan mengetahui laju degradasi beberapa jenis plastik menggunakan ulat hongkong (Tenebrio molitor L.) dan ulat jerman (Zophobas atratus F.) di Laboratorium. Penelitian dilaksanakan September 2020–Maret 2021 di Laboratorium Ekologi dan Sistematik, Fakultas Sains dan Teknologi Terapan, Universitas Ahmad Dahlan, Yogyakarta. Plastik yang digunakan yaitu Polypropylene (PP), High-Density Polyethylene (HDPE), dan Low-Density Polyethylene (LDPE) masing-masing sebanyak 1 gram. Perlakuan kontrol diberikan pakan dedak sebanyak 1 gram. Setiap ulat diukur bobot dan panjang tubuhnya setiap 3 hari sekali selama 30 hari. Hasil data yang diperoleh dianalisis secara statistik inferensial pada taraf kepercayaan 5%. Parameter yang diamati yaitu pertambahan panjang dan bobot larva, laju degradasi, dan waste reduction indeks (WRI). Nilai rerata panjang tertinggi T. molitor adalah HDPE (1,83 cm) dan terendah LDPE (1,41 cm). Pengukuran bobot tubuh menunjukkan nilai bobot yang seragam (0,07 gr). Pengukuran Z. atratus menunjukkan nilai rata-rata panjang tubuh tertinggi pada LDPE (3,70 cm) dan terendah pada HDPE (3,49 cm). Pertambahan bobot menunjukkan rata-rata berkisar antara 0,41–0,43 gram. Perhitungan nilai laju degradasi tertinggi dan terendah yaitu PP (0,011) dan HDPE (0,007) pada T. molitor. Perhitungan nilai laju degradasi tertinggi dan terendah pada Z. atratus adalah PP (0,032) dan HDPE (0,004). Nilai WRI tertinggi dan terendah pada T. molitor yaitu PP (0,36%) dan HDPE (0,22%), sedangkan pada Z. atratus yaitu pakan PP (1,08%) dan HDPE (0,12%). Kata kunci: Degradasi, HDPE, LDPE, Tenebrio molitor, Zophobas atratus